Relevance of Mohammed Arkoun's Thought in Reconstructing Contemporary Islamic Education - Saidah, Anis; Yunita, Ita; Fahmi, Muhammad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the application of Mohammed Arkoun’s critical thought in transforming contemporary Islamic education, with a specific focus on Indonesia. Arkoun’s Applied Islamology presents a multidisciplinary epistemological framework, integrating historical-critical analysis, hermeneutics, and deconstruction of traditional Islamic discourses. The study addresses the challenges posed by globalization, pluralism, and moral crises in education, and explores how Arkoun’s ideas can counteract rigid and dogmatic pedagogies by promoting critical reasoning, ethical awareness, and dialogical openness. Using a qualitative-descriptive method and literature-based analysis, the study examines Arkoun’s major works and related academic sources to understand the relevance and applicability of his thought to the Indonesian context. The findings indicate that Arkoun’s approach can provide a foundational framework for developing an inclusive, humanistic, and contextually relevant Islamic education system. However, the study also identifies challenges such as institutional conservatism, limited epistemic literacy among educators, and the lack of curriculum integration. To overcome these barriers, the study suggests strategies including teacher training in critical pedagogies, curriculum reform, and policy support for progressive educational models. Ultimately, Arkoun’s thought has the potential to drive the transformation of Islamic education into a space that fosters intellectual liberation, ethical reflection, and the promotion of pluralistic and democratic values.